Client-side ciphertext deduplication scheme with flexible access control. (13th October 2020) - Xie, Ying; Tian, Guohua; Yuan, Haoran; Jiang, Chong; Wang, Jianfeng
Data deduplication techniques with fine-grained access control have been applied to realise data sharing while saving the amount of storage space. However, many existing schemes can only achieve server-side deduplication, which greatly wastes the network bandwidth especially when the transmitted data is particularly large. Moreover, few existing schemes consider attribute revocation, in which the forward and backward secrecy cannot be guaranteed. To address the above problems, in this paper, we present a client-side ciphertext deduplication scheme with more flexible access control. Specifically, the data owners are divided into different domains and distributed corresponding domain keys through the secure channel, achieving proof of ownership in client-side deduplication. Besides, attribute revocation is realised through the proxy re-encryption, which need not preset the maximum number of clients in system initialisation phase. Security and performance analysis demonstrate that the proposed scheme can achieve desired security requirements while realising the efficient client-side deduplication and attribute revocation.